The role of vitamin D, omega acids, antioxidants, berberine, probiotics, lactoferrin and inositol in acne - Wioleta Faruga-Lewicka; Marek Kardas (Polish Pharmaceutical Society, 2023)
Introduction and objective Acne vulgaris is a common, chronic and inflammatory skin disease of the folliculopilosebaceous unit. According to the literature, acne affects 85% adolescents and 50% adulthood, with an increasing tendency. The symptoms of acne are skin lesions such as comedones, pustules, papules as well as nodules and they generally appear on face, shoulders, chest and back. Based on its severity acne can be divided into following categories: mild, moderate and severe. The pathogenesis of acne is multivariate. Significant importance is attributed to hormonal changes, the role of Cutibacterium acnes bacteria and the balance between C. acnes and Staphylococcus epidermidis, keratinization disorders, excessive sebum production, circadian rhythm disorders, a lot of stress in life and improper nutrition as a result of imbalanced diet. Finding the cause of acne is necessary to cure the disease. The study shows that supplementation seems to be a good solution in the case of acne vulgaris. The aim of the study was to present the most commonly used substances in supplements for acne skin, their properties and possibilities in the treatment of acne vulgaris. The intention of the authors was to draw attention to the possibilities of supplementing dermatological acne treatments with supplements. Pharmacists are often the first point of contact for acne vulgaris patients looking for a way to improve their skin condition. Review methods The PubMed database was reviewed for the most commonly used substances in therapy of acne skin. Publications from the period 2010-2022 were analyzed in terms of the following keywords: "vitamin D", "omega acids", "antioxidants", "berberine", "lactoferrin" and "inositol" in collocation with "acne". A review of 31 articles on the possibility of acne supplementation were reviewed. Supplementation of vitamin D, omega acids, antioxidants, berberine, probiotics, inositol and lactoferrin is discussed. Abbreviated description of the state of knowledge The effectiveness of taking supplements containing antioxidants, omega acids, berberine, probiotics, lactoferrin, inositol and vitamin D was discussed. Summary 1. Deficiencies of vitamin D3, vitamins A and E are often noted in patients with acne. 2. Supporting dermatological acne treatments with supplementation with omega acids and probiotics alleviates the side effects of treatment. 3. In the analyzed studies, there were no differences in the effectiveness of omega-3 acids compared to omega-6 acids in supplementation in patients with acne. 4. Multi-component preparations seem to be a better solution than supplements containing only one active ingredient. 5. More research is needed to be able to assess the real effectiveness of individual substances and determine their appropriate dosage.